Study guides

Q: What is t when 6t equals 12-2t?

Write your answer...

Submit

Related questions

t=1

6t 6(2) t=2 12 The answer is 12.

6t + 7 when t = -3 is 6*(-3) + 7 = -18 + 7 = -11

6t+t = 7t

t=-2

-47

(6t - 1) / 69 = 1 6t - 1 = 69 6t = 70 t = 70 / 6

8t + 5 = 6t + 1,subtract 6t an 5 from each side,2t = -4t = -2Checking, 8t + 5 = -16 + 5 = -11 and 6t +1 = -12 + 1 = -11

6t2 - 53t + 40 = 6t2 - 48t - 5t + 40 = 6t(t - 8) - 5(t - 8) = (t - 8)(6t - 5)

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6

Form the equation: 15-6t = 11t. Add 6t to both sides of the equation to obtain: 15 = 17t or 17t = 15. Divide both sides of the equation by 17 to obtain: t = 15/17.

(t + 7)(t - 1)

2r + 7r - 6t - r + 7t = 8r + t

If you mean: 6t -2 = 28 then the value of t is 5

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

t + 5t + 5 = 6t + 5

6t(t - 6)

12

-4t+5t-8+4=6t-4 eqn soln t=0 transpose variable terms on one side & constant terms on the other side of equality

It is an inequality in the single variable t.

For "6t - (2t2)", it is not reducible. For "(6t - 2t2)", it is 16t2

If A = T and T = U then A = U.

5r x 6t = 30rt

As an algebraic expression it is simply: 6t+5

6t -2t + 5u = 4t - 5u